Mn, Cu and Cr nanoparticles in Li2B4O7 glass: Radiation shielding and optical properties. (May 2022) - Elias, Janet A.; Montes, Eduardo; Torres-Castro, Alejandro; Wiechers, Carlos; Gomez-Solis, C.; Vega-Carrillo, Hector Rene; Sosa, Modesto A.; Vallejo, M.A.
Abstract: Lithium tetraborate (Li2 B4 O7 ) glass matrices doped with Manganese (Mn), Copper (Cu) and Chromium (Cr) were synthesized, using the melt-quenching method. Radiation shielding and optical parameters are studied in this work. High-resolution Transmission Electron Microscopy confirms formation of Mn, Cu and Cr nanoparticles in the samples. Absorption spectra of the samples show the characteristic surface-plasmon bands of these transition-metals nanoparticles. Their bandgaps were calculated from the absorption spectra. The fluorescence bands of each transition-metal nanoparticle ensembles in the tetraborate glass matrices are identified by recording the fluorescence spectrum. Emission spectra under 405 nm pumping show bands with a peak at 591 nm from nanoparticles of Mn, a peak at 750 nm of Cu, and a peak at 735 nm of Cr. The fluorescence lifetimes are measured, and the stimulated emission and absorption cross-section are calculated. The theoretical values of radiation shielding parameters mass attenuation coefficient (MAC), half value layer (HVL), tenth value layer (TVL), mean free path (MFP) and effective atomic number ( Z eff ) were calculated for the glass samples to analyze which sample has the best radiation shielding response. It should be noted that the samples made in this work present a better response than high-performance heavyweight concrete mixes using the coarse aggregates of magnetite. Highlights: Li2 B4 O7 glass matrices doped with Mn, Cu and Cr were synthesized. Radiation shielding and optical parameters are studied. Absorption show characteristic surface-plasmon bands of metal nanoparticles. The theoretical values of radiation shielding parameters were calculated. Samples in this work present better response than some heavyweight concrete mixes.